Analisis Pengalaman Belajar Siswa Dalam Melaksanakan Praktik Kerja Industri - Rani Ayu Agustina; Ngatou Rohman (Nozel : Jurnal Pendididikan Teknik Mesin, 2026)
This study aims to analyze students’ learning experiences during Industrial Work Practice (Prakerin), particularly in the development of hard skills and soft skills. This research used a qualitative descriptive approach conducted at SMK Negeri 2 Surakarta involving students, supervising teachers, and industrial mentors. Data were collected through interviews, observation, and documentation, then analyzed using interactive analysis techniques. The results show that Prakerin contributes to the improvement of students’ technical competencies such as vehicle maintenance and repair, as well as non-technical competencies including discipline, communication, teamwork, and adaptability to industrial work culture. Although several challenges were encountered, guidance from mentors supported students’ development. Overall, Prakerin plays an important role in enhancing students’ work readiness.Keywords: industrial work practice, vocational education, hard skills, soft skills